Corporate Social Responsibility Regarding Education of Foreign Direct Investment Companies in Vietnam - Pham, Thu Huong; Pham, Huong Quynh (Journal of International Economics and Management, 2019)
Foreign Direct Investment (FDI) has been growing rapidly in Vietnam despite globally complicated and unpredictable fluctuations of the economy. Although it is presented in impressive numbers regarding FDI’s overall efficiency in Vietnam, the connection between FDI businesses and Vietnam’s education and training is rather feeble. This paper investigates the FDI companies’ corporate social responsibility (CSR) performance regarding education development in Vietnam. The most popular methods of performing CSR regarding education include granting scholarship, building schools and education centers, providing and improving educational facilities, developing programs for young talents, sponsoring scientific researches… CSR regarding to education of FDI companies in Vietnam has impacted on efforts in integrating CSR in their daily operation of big local businesses with mindsets of going global quickly. However, most FDI companies consider CSR regarding education as a part of PR campaigns and do not have a long-term vision for their CSR activities. Methods, targets and locations of these activities are still narrow and centralized, resulting in a restricted number of people reached. Most CSR activities to improve education conditions are available to students in big urban cities, while the real population in need is left inadequately approached. This paper proposes some recommendations for improving CSR activities regarding education of FDI companies in Vietnam.